2001
DOI: 10.1063/1.1425453
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light-emitting diodes at 340 nm using quaternary AlInGaN multiple quantum wells

Abstract: An ultraviolet light-emitting diode with peak emission wavelength at 340 nm is reported. The active layers of the device were comprised of quaternary AlInGaN/AlInGaN multiple quantum wells, which were deposited over sapphire substrates using a pulsed atomic-layer epitaxy process that allows precise control of the composition and thickness. A comparative study of devices over sapphire and SiC substrates was done to determine the influence of the epilayer design on the performance parameters and the role of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 19 publications
0
38
0
1
Order By: Relevance
“…1,2 However, up to now the research focus has primarily been GaN, ternary InGaN, AlGaN, and quaternary AlInGaN alloys with optical transitions in the 280-550 nm range. [3][4][5] Molecular beam epitaxy or metalorganic chemical vapor deposition ͑MOCVD͒ techniques were primarily used to grow the studied high-quality films and quantum structures on substrates such as sapphire, SiC, or bulk GaN. To push the optical emission/detection wavelength to the deep UV region (xр280 nm) high-quality Al x Ga 1Ϫx N alloys with Al-mole fractions in excess of x ϭ0.5 are needed.…”
mentioning
confidence: 99%
“…1,2 However, up to now the research focus has primarily been GaN, ternary InGaN, AlGaN, and quaternary AlInGaN alloys with optical transitions in the 280-550 nm range. [3][4][5] Molecular beam epitaxy or metalorganic chemical vapor deposition ͑MOCVD͒ techniques were primarily used to grow the studied high-quality films and quantum structures on substrates such as sapphire, SiC, or bulk GaN. To push the optical emission/detection wavelength to the deep UV region (xр280 nm) high-quality Al x Ga 1Ϫx N alloys with Al-mole fractions in excess of x ϭ0.5 are needed.…”
mentioning
confidence: 99%
“…In particular, the PALE technique allowed us to fabricate LEDs emitting at wavelengths as short as 305 nm [6]. It has also been demonstrated that incorporation of indium into AlGaN decreases potential fluctuations and increases the diffusion length of photoexcited carriers [7], as well as markedly enhances UV emission [8][9][10].In spite of strong implications for the crucial role of indium in improving the radiative properties of nitride alloys with high Al molar fraction, the physical reasons of this phenomenon are not completely understood. To clarify the underlying physics of light emission from quaternary AlInGaN alloys, we examined the variation of photoluminescence temperature behavior with gradual incorporation of In into AlGaN.…”
mentioning
confidence: 97%
“…Similar longwavelength peaks in EL spectra were also observed in previous reports of AlGaN-based deep UV LEDs emitting at 325 nm and 340 nm. [6][7][8] These long-wavelength peaks arise from the radiative recombination involving deep levels. To determine their origin, we studied the transient behavior of both the 285 nm and the 330 nm EL peaks.…”
mentioning
confidence: 99%